Qanā’ah sebagai Solusi Etis-Spiritual dalam Menghadapi FOMO: Telaah Tafsir Fī Ẓilāl al-Qur’ān Sayyid Quthb atas Surah Ṭāhā Ayat 131 - Saifullah; Nurul Hasyqin; Kasmuri; Nixson (Universitas Darussalam Gontor, 2026)
This study explores Sayyid Quthb's interpretation of contentment in Surah Ṭāhā verse 131 through the interpretation of Fī Ẓilāl al-Qur’ān, while also revealing its relevance as a moral basis for dealing with the phenomenon of Fear of Missing Out (FOMO) in the digital age, namely the era of socio-cultural transformation marked by the massive penetration of digital technology into all aspects of human life including how to interact, communicate, and construct self-identity through social media. The main focus needs to be directed at the role of contentment. This attitude is a spiritual remedy for social anxiety triggered by the habit of comparing oneself on social media. The study adopts a descriptive-analytical approach based on literature study. The main data comes from the text of the Qur'an Surah Ṭāhā (20): 131. To strengthen the analysis, this study not only refers to Sayyid Quthb's thoughts in Fī Ẓilāl al-Qur’ān, but also attempts to dialogue with various other tafsir books. The main contribution of this study lies in exploring the relevance of Sayyid Qutb’s thoughts in Fī Ẓilāl al-Qur’ān to address contemporary mental issues, particularly the phenomenon of FOMO. By making the concept of qanā’ah as a meeting point, this study attempts to open a space for dialogue between Sayyid Qutb’s interpretation and the spiritual needs of digital society, while acknowledging that enrichment from various other interpretive perspectives is still very necessary for a more comprehensive understanding